Pelarutan P dan K dari batuan leusit dan apatit menggunakan kombinasi senyawa humat-BPF-BPK - Mohammad Jimmy KURNIATA; Tri Candra SETIAWATI; Jay JAYUS (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2019)
AbstractDue to the limited availability of potassium and phosphate in soil and the high price of their synthetic mineral fertilizers, the importance of minerals-solubilizing microorganismshas been increasingly significant aimed at sustainable agriculture achievement. Apatite and leucite are considerably abundant minerals; however, their solubility is low. This study was aimed to study the effects of the combination of phosphate-and potassium-solubilizing bacteria (PhSB and PSB) and humic acid of cassava as bioleaching agents in the solubilization process of potassium and phosphate from agromineral material. Some leucite agromineral materials were obtained from Situbondo and Pati, while apatite materials were obtained from Tuban and Ciamis, Indonesia. The minerals were treated with 2.10 x 107CFU/g PhSB and 1.61 x 107CFU/g PSB isolates, combined with 100 ppm organic C humic compounds from cassava as the media. The minerals solubility was monitored every two weeks for 12 weeks ofobservation, which includes the concentration of dissolved K and P, as well as the pH of the media. The presence of organic acids was observed to monitor the bacterial activity by using HPLC, while the physical changes of the rock surface due to bacterial dissolution were scanned by using scanning electron microscopy (SEM). The results showed that the highest dissolution of P was recorded at week 4 (344.23 ppm) released from Tuban apatite with the combination of PhSB and PSB under the humic compound.In contrast, the highest K dissolution was obtained at week 6 for Situbondo leucite (44.21 me/100 g) with a combination of humic cassava compound and PSB only. Statistical analyses showed a mark different on both minerals for dissolution of K and P. The SEM result indicates breakage of the rock surface after a three month observation period indicating that the dissolution minerals occurred. Selected organic acids such as citric, ferulic, coumaric, syringic, and malic acids were detected during the treatment.[Keywords: leucite, apatite, humic compounds, organic acid] Abstrak Ketersediaan kalium (K) dan fosfat (P) dalam tanah terbatas,danharga pupuk sintetik relatif mahal, menjadikan mikroorganismepelarut mineral memegang peranan penting dalam menunjang pertanian berkelanjutan.Batuan mineral apatit dan leusitmerupakan sumber daya mineral dengan ketersediaan tinggi tetapi mempunyai kelarutan mineral rendah. Penelitian bertujuan untukmempelajari pengaruh kombinasi bakteri pelarut fosfat (BPF), bakteri pelarut kalium (BPK), dan humatsingkong sebagai agen bioleachingdalam proses pelarutan K dan P dari bahan agromineral. Bahan agromineral leusitdiperoleh dariKabupatenSitubondo dan Pati, sedangkan bahan apatit berasal dari Kabupaten Tuban dan Ciamis, Indonesia. Bahan mineral diperlakukan dengan 2,10 x107CFU/gBPF dan 1,61 x 107CFU/gBPK, dikombinasikan dengan 100 ppm C organik senyawa humatdari singkong sebagai media. Kelarutan mineral diamati setiap dua minggu sekali selama 12 minggu meliputi kelarutan K dan P, dan pH media. Produksi asam organik dianalisis untuk mengamati aktivitas bakteri menggunakan HPLC dan perubahan fisik permukaan batuan akibat pelarutan bakteri dipindai menggunakan SEM.Hasil penelitian menunjukkan bahwa pelarutan fosfat tertinggi tercatat pada minggu ke 4 (344,23 ppm) yang dilepaskan dari apatit Tuban dengan kombinasi BPF dan BPK dengan senyawa humat, sedangkan pelarutan kalium tertinggi diperoleh pada minggu ke 6 dari leusitSitubondo (44,21 me / 100 g) dengan kombinasi senyawa humatsingkong dan BPK. Secara statistikpada kedua mineral pelarutan K dan P menunjukkan berbedanyata. Hasil analisis dengan menggunakan SEMterjadi kerusakan permukaan batuansetelah periode pengamatan tigabulan yang menunjukkan bahwa terjadi pelarutan mineral. Selama percobaan dideteksi beberapa asam organik seperti asam sitrat, ferulat, kumarat, siringatdan malat. [Kata kunci: leusit, apatit,senyawa humat,asam organik]